Shopping for Health: Fruit - Ashley R. Kendall; Wendy J. Dahl (EDIS)
Fruits taste good, and they are good for you. Some fruits are very nutrient dense. This means they contain lots of the vitamins, minerals, antioxidants, and fiber that your body needs to stay healthy. Whether you like fresh fruit or fruit juice, frozen fruit or fruit from a can, it’s important to choose a variety of different fruits every day. Here are some tips to help you before, during, and after your fruit shopping trip. This 3-page fact sheet was written by Ashley R. Kendall and Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, March 2013.